2001
DOI: 10.1080/00034980020035898
|View full text |Cite
|
Sign up to set email alerts
|

Immunological alterations associated with Plasmodium vivax malaria in South Korea

Abstract: Various haematological and immunological studies on patients infected with Plasmodium vivax were undertaken, at diagnosis (day 0), after treatment with chloroquine but during primaquine treatment (day 10) and after all treatment (day 59), in South Korea (where there has been a recent and abrupt increase in the incidence of such infection). The main aims were to gain an understanding of the haemto-immunological alterations of this malarial infection, both before and after treatment, and to identify at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Consistent with previous investigations [7,9,11,31,32] a decrease in WBC counts was associated with malaria infection while Ladhani et al [33] reported children with malaria to have a higher WBC count. The mean WBC counts in the pupils highlights a significant interaction between the age, parasite density and the altitude.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous investigations [7,9,11,31,32] a decrease in WBC counts was associated with malaria infection while Ladhani et al [33] reported children with malaria to have a higher WBC count. The mean WBC counts in the pupils highlights a significant interaction between the age, parasite density and the altitude.…”
Section: Discussionsupporting
confidence: 90%
“…Previous findings show the inhibition of B cell phenotypes in both P. falciparum and P. vivax infections [24], [42], [43]. In addition, our results showed the level of B cells in acute P. vivax -infected patients was unchanged.…”
Section: Discussionsupporting
confidence: 63%
“…One of the most striking results from the study was the low levels of platelet and plateletcrit (a measure of total platelet mass) observed in malaria-infected study participants compared to uninfected participants, a finding that is consistent with results from other studies 6 , 7 , 16 . This observation is particularly common in Plasmodium falciparum 4 , 30 and Plasmodium vivax infections 31 , 32 . In this present study, 58.1% of malaria-infected individuals were thrombocytopaenic.…”
Section: Discussionmentioning
confidence: 94%